Exploring the Sustainability of Environmentally Friendly Alternative Materials in Building Construction - Manurung, Joevanka Abigail (IHSA Institute, 2024)
This research investigates the use of environmentally friendly alternative materials in building construction, aiming to provide a comprehensive analysis of their benefits, challenges, and implications. Through a mixed-methods approach combining literature review, surveys, interviews, and case studies, the study explores the environmental, economic, and social impacts of green materials, as well as the barriers to their adoption. The findings reveal significant environmental benefits associated with sustainable materials, including reduced carbon emissions, resource conservation, and improved indoor environmental quality. Performance analyses demonstrate that green materials often match or exceed the durability and functional performance of traditional materials, while economic assessments indicate long-term cost savings despite higher initial investments. Moreover, sustainable construction practices have positive social impacts, such as improved occupant health and well-being, job creation, and community resilience. The research concludes with recommendations for overcoming barriers to adoption, including investment in research and development, providing financial incentives and policy support, increasing education and training programs, and conducting public awareness campaigns. By implementing these recommendations, the construction industry can accelerate the transition towards sustainable construction practices, creating a more resilient, healthy, and sustainable built environment for future generations.